The Complexity and Consequences of The Policy Implementation Omnibus Law Creation on Welfare of Contract Workers In Indonesia - Borman, M Syahrul; Marwiyah, Siti; Cornelis, Vieta Imelda; Vansya, Muhammad Ahnaf Maulana; Ramdan, Muhammad; Aranggraeni, Renda; Makhtar, Maheran (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2026)
The Omnibus Law on Job Creation is a significant piece of regulatory reform introduced by the Indonesian government to boost investment competitiveness and stimulate economic growth by streamlining cross-sector regulations, including labour law. However, the reform has sparked debate about whether workers, particularly contract workers who are vulnerable in the labour market, are adequately protected by the law. This research aims to analyse the complexities surrounding the implementation of the Omnibus Law on Job Creation and its implications for the welfare and legal protection of contract workers in Indonesia. This research employs a qualitative legal approach, using document analysis and network content analysis of industrial relations dispute decisions issued by the Supreme Court of the Republic of Indonesia between 2020 and 2024. NVivo 12 Plus was used to support systematic coding and visualisation. The results indicate that, while regulatory changes under the Omnibus Law increase labour market flexibility, they also create legal uncertainty for contract workers, affecting income stability, employment security and access to labour rights. It is concluded that the policy creates an imbalance between investment-oriented objectives and the constitutional mandate to protect workers' welfare. Therefore, a regulatory review and a more inclusive policy formulation process are necessary to ensure fair and sustainable labour protection.